Anodic Stripping Voltammetric Procedure of Thallium(I) Determination by Means of a Bismuth-Plated Gold-Based Microelectrode Array - Mieczyslaw Korolczuk; Mateusz Ochab; Iwona Gęca (Sensors, 2024)
This article presents a new working electrode based on a bismuth-plated, gold-based microelectrode array, which is suitable for determining thallium(I) species using anodic stripping voltammetry (ASV). It allowed a significant increase in the sensitivity as compared to other voltammetric sensors. The main experimental conditions and the instrumental parameters were optimized. A very good proportionality between the Tl(I) peak current and its concentration was evidenced in the range from 5 × 10−10 up to 5 × 10−7 mol L−1 (R = 0.9989) for 120 s of deposition and from 2 × 10−10 up to 2 × 10−7 mol L−1 (R = 0.9988) for 180 s. A limit of detection (LOD) of 8 × 10−11 mol L−1 for a deposition time of 180 s was calculated. The effects of interfering ions on the Tl(I) analytical signal were studied. The proposed method was applied for quantitative Tl(I) detection in water certified reference material TM 25.5 as well as in spiked real water samples, for which satisfactory recovery values between 98.7 and 101.8% were determined.